Between entrepreneurial neotechnicism and teaching authority (Revista Contexto & Educação, 2024)
Entrepreneurial neotechnicism, understood as access and management of information and communication technologies in their primary aspect of socialization, added to a pragmatic reading of social activities, influence the new educational contexts.At this conjuncture, teaching authority has declined, since it is removed from the central role of the educational process, being increasingly replaced by technological devices. Also its authority declines, as the knowledge holder on educational curricula objects, as everyone has access to information in the palm of their hand, through smartphones, for example. By analyzing this theme, the present work sought to answer the following question: between the past and the future, what challenges are posed for the exercise of the educator's craft in the present? Answering this question, a bibliographic research was carried out, as main theoretical references Jean Jacques Rousseau (1995) and Hannah Arendt (2007). From the understanding of the teacher's role according to the philosophical perspectives of Rousseau and Arendt, it is opposed to the challenges faced by educators in contemporary society to exercise their social function. These philosophical perspectives allowed attributing value to the educator role in the new contexts, reaffirming the figure of the governing educator, social and pedagogical authority, responsible for human formation for common life and for a democratic society.
Keywords: authority; governance in education; entrepreneurial neotechnicism; Rousseau; Hannah Arendt